Teachers’ Emotional Intelligence and Its Influence on Learners’ Behavioral Development - Amosco, Nizel; Casinillo, Fate; Payod, Marianne Irish; Malabago, Nolasco; Mustafa, Khalid; Neri, Remcil (International Journal of Educational Studies, 2025)
This research explores the relationship between teachers’ emotional intelligence and student behavior in an educational setting, focusing on key behavioral aspects such as emotional regulation, social skills, respectful behavior, and engagement. Emotional intelligence, which encompasses self-awareness, self-regulation, motivation, mental health first aid skills, and relationship management, is believed to play a significant role in fostering a positive learning environment. However, the findings revealed no statistically significant relationship between the emotional intelligence of teachers and students’ behavior, as all p-values exceeded the 0.05 threshold. Despite the high levels of emotional intelligence among teachers, the study suggests that these competencies do not directly influence student behavior in the areas assessed. The research emphasizes the importance of bridging the gap between emotional intelligence and its practical application in classrooms. Based on the findings, a development program is proposed to enhance teachers’ ability to leverage their emotional intelligence effectively, focusing on training in classroom management, student engagement strategies, and fostering respectful and collaborative learning environments. The program aims to provide actionable insights and tools for teachers to translate emotional intelligence into impactful teaching practices that positively shape student behavior. This study underscores the need for further research into other factors influencing student behavior and calls for targeted interventions that integrate emotional intelligence with practical pedagogical approaches. The findings and proposed program provide valuable guidance for educators and administrators striving to improve student outcomes through teacher professional development.